1999
DOI: 10.1080/095006999290822
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual change in science through collaborative learning at the computer

Abstract: The purpose of this classroom study was to investigate whether and how collaborative learning at the computer fosters conceptual change. A suite of computer simulation programs was developed to confront students' alternative conceptions in mechanics. This was integrated into a 10-week physics instruction of a Grade 10 science class in a Melbourne high school. A Conceptual Test was administered to the class as a pre-, post-and delayed post-test to determine students' conceptual change. Students in the class wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
7

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 27 publications
1
49
0
7
Order By: Relevance
“…It has been shown that students who co-construct (Hogan, Nastasi, & Pressley, 1999;Tao & Gunstone, 1999) ideas have been more successful in extending the knowledge of their peers than students who work independently on solving a problem. Identification of such processes in a collaborative learning environments would allow us to understand the degree to which these students work with each other.…”
Section: Independent Vs Joint Construction Of Knowledgementioning
confidence: 99%
“…It has been shown that students who co-construct (Hogan, Nastasi, & Pressley, 1999;Tao & Gunstone, 1999) ideas have been more successful in extending the knowledge of their peers than students who work independently on solving a problem. Identification of such processes in a collaborative learning environments would allow us to understand the degree to which these students work with each other.…”
Section: Independent Vs Joint Construction Of Knowledgementioning
confidence: 99%
“…Within research on science learning and conceptual change about science, there is interest in collaboration in general and social constructivism in particular (Chen & She, 2012;Tao & Gunstone, 1999;Luebeck & Bice, 2005;.…”
Section: Conceptual Change Using An Online Discussionmentioning
confidence: 99%
“…While the theoretical frameworks of studies into conceptual change often address students' learning processes, the majority of the empirical procedures investigate the products of students' learning rather than the processes of student conceptual development or conceptual change. Thus, from the current status of research, it can be concluded that major issues of understanding the processes by which conceptual development takes place are still theoretically and empirically vague (Aufschnaiter et al, 2008;Mercer, 2008;Ravenscroft, McAlister, & Sagar, 2012;Tao & Gunstone, 1999). Generally, we cannot yet explain in detail why teaching strategies that attempt to promote conceptual change are often unsuccessful.…”
Section: Introductionmentioning
confidence: 95%
“…Each placemark can be represented with different shapes and colors, which are available in the Google Earth application ( Figure 5A). As each stop is saved in "kmz" format, when you open the file, the Google Earth platform opens and automatically georeferences a stop [14,22]. Subsequent geological mapping in Google Earth was loaded into ortho overlap, in which a user can zoom "+" or "−" to approach or move away from a geosite to analyze the geological context of the sector study and provide a spatial overview of the itinerary, which is displayed using different 3D geological materials by observing their topographic position and lithologic sequences.…”
Section: Preparation Of Itinerary Using Google Earth and 3d Virtual Fmentioning
confidence: 99%
“…As the geological analysis of a natural area is challenging from the perspective of space [12,13], we employ maps to observe the distribution of different materials and geological elements [14,15]. Technological advances enable free applications that can be implemented with a computer [16] an overview of the three-dimensional-3D-territory with different stops and geoeducational pathways and the deployment of geological mapping and other thematic maps on orthophotos, which display the different elements (i.e., roads and towns) that guide students to their locations [17][18][19].…”
Section: Introductionmentioning
confidence: 99%